Implementation of the merit system for position placement in government Papua province - Jonatan Dionisius Swaimer Morin; Dadang Suwanda; Haikal Ali (Sean Institute, 2024)
This research aims to find out and analyze the implementation of the merit system for position placement in the Papua Provincial Government and to find out and analyze the barriers and efforts made by the Papua Province Regional Civil Service Agency in implementing the merit system. This research uses descriptive research methods. A qualitative approach is used in this research method, because the data produced in this research is in the form of written and spoken words. Based on the research results, it shows that: 1). The implementation of the Merit System for Position Placement in the Papua Provincial Government can be said to be still in the process of being implemented in a better direction. Of the 5 existing aspects, only 3 can be said to be optimal, namely the Work Performance, Competency and Promotion aspects. And there are 2 aspects that are still inappropriate, namely Position Qualifications and Managerial Competencies that are not appropriate, and there are no regulations regarding the implementation of the merit system in the Papua Provincial Government, 2). Inhibiting factors in implementing the merit system for position placement in the Papua Provincial Government include: lack of employment/abk data, quality of human resources that does not match competency and potential, lack of adequate facilities, absence of regulations from the regional government related to merit system guidelines. The efforts made to overcome the inhibiting factors in implementing the merit system for position placement in the Papua Provincial Government include completing the anjab/abk data, improving the quality of human resources, providing adequate facilities that can support it, and making regulations related to the implementation of the merit system.